2020
DOI: 10.2340/00015555-3619
|View full text |Cite
|
Sign up to set email alerts
|

Significant Differences in the Bacterial Microbiome of the Pharynx and Skin in Patients with Psoriasis Compared with Healthy Controls

Abstract: Studies have shown differences in the skin and gut bacterial microbiomes in patients with psoriasis, but the pharyngeal microbiome has not been studied previously. The aim of this study was to investigate differences in the bacterial microbiome of the pharynx and skin of patients with psoriasis compared with healthy controls. Swabs were taken from the pharynx and elbow skin of 39 patients with psoriasis and 70 controls. Microbiomes were characterized by sequencing 16S rRNA genes on the Illumina MiSeq platform.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
1
13
0
2
Order By: Relevance
“…Similar to other previous studies of psoriasis skin composition ( Alekseyenko et al, 2013 ; Chang et al, 2018 ), our results showed the three commonest prominent phyla in psoriatic skin: Proteobacteria , Firmicutes , and Actinobacteria . In the psoriatic pharyngeal habitat, the majority of bacteria were identified within the phyla Firmicutes and Bacteroidetes , in agreement with previous studies ( Assarsson et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Similar to other previous studies of psoriasis skin composition ( Alekseyenko et al, 2013 ; Chang et al, 2018 ), our results showed the three commonest prominent phyla in psoriatic skin: Proteobacteria , Firmicutes , and Actinobacteria . In the psoriatic pharyngeal habitat, the majority of bacteria were identified within the phyla Firmicutes and Bacteroidetes , in agreement with previous studies ( Assarsson et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…The microbiota of the skin or pharynx of patients with psoriasis and healthy controls has already been demonstrated to differ significantly ( Assarsson et al, 2020 ; Olejniczak-Staruch et al, 2021 ). In order to investigate the microbiota community structure of patients with PP and GP, we examined the relative abundances of LPP, SPP, and GP samples by stacked bar plots to determine the predominant composition among these groups ( Supplementary Figures 3A,D ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After assessing the full text, 1 more study also has been excluded as it explains more about faecal microbiota translational research in psoriasis-like inflammation in mice and did not accord with the objective of present meta-study. Therefore, we reviewed twenty research articles (PMID: 33796091, 21 24451201, 22 18648509, 23 29199351, 24 26811697, 25 16891514, 26 25510344, 27 32945341, 28 31619666, 29 32852562, 30 30185226, 15 30985920, 31 29559344, 32 26659932, 33 22065152, 34 28649415, 35 24018484, 36 31247199, 37 31228520, 38 32486022 16 ) thoroughly that focus on skin microbiota dysbiosis of the lesional and normal psoriatic skin.…”
Section: Resultsmentioning
confidence: 99%